Knowledge-based Utilization in Organizational IT Support. A Case Study at BPS-Statistics Indonesia - Herlambang Permadi; Dana Indra Sensuse (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Many problems in the IT sector are experienced by employees in carrying out daily government activities. The problems faced often disrupt government activities in providing services to the community. This study analyzes the IT problems that are often found in organizations and their impacts. As many as 43 people have participated in the survey to identify what problems are often experienced and the impact they have had. The survey started with 7 IT service groups and produced 37 IT problems. The result is an implementation of a knowledge-based system that can help employees in solving IT problems on their own in their work environment.